Unrevealing Lithium Repositioning in the Hallmarks of Cancer: Effects of Lithium Salts (LiCl and Li2CO3) in an In Vitro Cervical Cancer Model - Juan Carlos García-Acosta; Alejando Israel Castillo-Montoya; Gareth Omar Rostro-Alonso; Edgar Yebrán Villegas-Vázquez; Laura Itzel Quintas-Granados; Luis Sánchez-Sánchez; Hugo López-Muñóz; Lizbeth Cariño-Calvo; Israel López-Reyes; Lilia Patricia Bustamante-Montes; Gerardo Leyva-Gómez; Hernán Cortés; et al. (Molecules)
Lithium, a natural element, has been employed as a mental stabilizer in psychiatric treatments; however, some reports indicate it has an anticancer effect, prompting the consideration of repurposing lithium for cancer treatment. The potential anticancer use of lithium may depend on its form (salt type) and the type of cancer cells targeted. Little is known about the effects of Li2CO3 or LiCl on cancer cells, so we focused on exploring their effects on proliferation, apoptosis, migration, and cell cycle as part of the hallmarks of cancer. Firstly, we established the IC50 values on HeLa, SiHa, and HaCaT cells with LiCl and Li2CO3 and determined by crystal violet that cell proliferation was time-dependent in the three cell lines (IC50 values for LiCl were 23.43 mM for SiHa, 23.14 mM for HeLa, and 15.10 mM for HaCaT cells, while the IC50 values for Li2CO3 were 20.57 mM for SiHa, 11.52 mM for HeLa, and 10.52 mM for HaCaT cells.) Our findings indicate that Li2CO3 and LiCl induce DNA fragmentation and caspase-independent apoptosis, as shown by TUNEL, Western Blot, and Annexin V/IP assay by flow cytometry. Also, cell cycle analysis showed that LiCl and Li2CO3 arrested the cervical cancer cells at the G1 phase. Moreover, lithium salts displayed an anti-migratory effect on the three cell lines observed by the wound-healing assay. All these findings imply the viable anticancer effect of lithium salts by targeting several of the hallmarks of cancer.